REFUGEES FROM NAZI GERMANY: ILLEGAL BORDER CROSSING TO USSR IN 1939–1941 (Південний архів (історичні науки), 2025)
The purpose of the study is to point out the social, political and legal peculiarities that forced people to illegally cross the border between Nazi Germany and the USSR in 1939–1941. The investigation is based on unpublished documents from the State Archives of Lviv Region (DALO) and the State Archives of the Security Service of Ukraine (SBU State Archives). Criminal cases against persons convicted by special meetings at the MGB (MVS) of the USSR were investigated. Methods. The fundamental principles of the proposed scientific research are: historicism, objective analysis of events and facts, regardless of political or ideological layers.The basis of the research is the use of historical, logical, systemic and structural methods. We will also use the following scientific methods: analytical, chronological and biographical. The use of these methods will contribute to the analysis of a specific problem of historical research. Results. The question of how the international law of the interwar period and the current practice of interstate relations interpreted the right of nations to self-determination and the formal requirements for its implementation is also important for the analysis of the needs and opportunities of the population to exercise mobility. The article examines pecuriarities of illegal border crossing in 1939–1941 between the USSR and Nazi Germany. Specific examples of punishments for violating the border established by totalitarian countries are given. Interstate European borders in many cases did not correspond to the parameters of ethnic demarcation in the period between the two world wars; outside the borders of national states were millions of inhabitants, primarily of those peoples whose interests were not taken into account at the Versailles Conference. Numerous cases of refugees appearing in the USSR from territories controlled by Nazi Germany occurred as early as the fall of 1939. Conclusions. Conclusion about the repressive activities of the Soviet totalitarian regime is based on the results of the analysis of archival materials. It is consisted in severe punishment of refugees and those who needed temporary protection from the Nazi policy of Hitler's Germany. The analysis of criminal cases makes possible to analyze in details the motives of the refugees, their path and further fate. The consideration of individual cases confirmed the political motivation of investigative and judicial bodies, as well as the repressive and punitive system in the USSR. In this article we also take in to account the previous totalitarian experience of social and legal relations in Nazi Germany. Thousands of Jews, sometimes uniting in groups of several dozen people, set off for the USSR because of that. Such refugees from repression often faced a a new meeting with state security agencies in the Soviet Union. Sometimes, on charges of “illegal border crossing,” those convicted received from three to eight years in labor camps. Some of them did not survive. The Soviet and Nazi totalitarian regimes used refugees for their political goals, homogenizing society and intimidating the rest of the citizens.
Keywords: refugees, World War II, totalitarian regime, repressions, illegal border crossing